Peer facilitators’s role to support pregnant women in utilizing HIV services during the COVID-19 pandemic - Artha Camellia; Plamularsih Swandari; Irwanto Irwanto; Gusni Rahma; Tuti Parwati Merati (International Journal of Public Health Science (IJPHS), 2023)
Human immunodeficiency virus (HIV) prevalence on pregnant women in Indonesia is estimated around 0.3%. The prevention of mother-to-child disease transmission (PMTCT) program has been implemented nationally since 2008, though, less than 50% of the total pregnant women each year get an HIV test and only 18% of those who are HIV positive get antiretroviral (ARV) treatment until now. COVID-19 pandemic, occurred since 2019, has brought significant changes to public health aspects including the utilization of HIV services. This study is aimed to determine factors influencing the PMTCT program services utilization during pandemic. This study used mix method approach with quantitative approach using a cross-sectional study design (174 HIV mothers from six provinces in Indonesia) and qualitative approach with in-depth interviews of 13 informants consisting of HIV mothers, health workers, program holders and peer facilitators. The results showed the HIV services utilization during pandemic was 52.3%. The most influenced factor was peer facilitators support (POR 2.96; 95% CI=1.45-6.03), HIV mothers who did not receive assistance from peer facilitators had 2.96 times chance of not utilizing the services compared to them who received. It requires to strengthen cooperation between health services and peer facilitators to support HIV mothers in accessing HIV services.